2014
DOI: 10.1016/j.vph.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interleukin-1 on cardiac fibroblast function: Relevance to post-myocardial infarction remodelling

Abstract: The cardiac fibroblast (CF) is a multifunctional and heterogeneous cell type that plays an essential role in regulating cardiac development, structure and function. Following myocardial infarction (MI), the myocardium undergoes complex structural remodelling in an attempt to repair the damaged tissue and overcome the loss of function induced by ischemia/reperfusion injury. Evidence is emerging that CF play critical roles in all stages of post-MI remodelling, including the initial inflammatory phase that is tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 85 publications
(131 reference statements)
0
42
0
Order By: Relevance
“…Thus, CF may contribute to the inflammatory milieu that occurs in the myocardium early after MI [10,95]. In addition to this inflammatory response, we [7,88,93,94,[96][97][98] and others [61,99,100] have demonstrated that CF alter the balance of cardiac ECM turnover in favour of degradation in response to IL-1; for example by increasing secretion of MMPs, decreasing collagen synthesis and decreasing expression of profibrotic factors (e.g. connective tissue growth factor).…”
Section: Interleukin-1mentioning
confidence: 79%
See 3 more Smart Citations
“…Thus, CF may contribute to the inflammatory milieu that occurs in the myocardium early after MI [10,95]. In addition to this inflammatory response, we [7,88,93,94,[96][97][98] and others [61,99,100] have demonstrated that CF alter the balance of cardiac ECM turnover in favour of degradation in response to IL-1; for example by increasing secretion of MMPs, decreasing collagen synthesis and decreasing expression of profibrotic factors (e.g. connective tissue growth factor).…”
Section: Interleukin-1mentioning
confidence: 79%
“…Thus, IL-1 is emerging as a potentially important therapeutic target for controlling both inflammatory and fibrotic responses after MI through effects on CF [88]. A similar role for IL-1 in atherosclerosis has also been proposed [101], making IL-1-selective inhibitory strategies an attractive proposition for treating a range of cardiovascular diseases.…”
Section: Interleukin-1mentioning
confidence: 95%
See 2 more Smart Citations
“…IL-1 is a proinflammatory cytokine whose levels are increased in the heart early after myocardial infarction and can modulate many cellular functions of CF that are pertinent to cardiac remodelling [27]. Using real-time RT-PCR we assessed the influence of T2DM on mRNA expression of several pertinent genes at basal level and following treatment with IL-1.…”
Section: Influence Of T2dm On Basal and Il-1 Induced Gene Expressionmentioning
confidence: 99%